(untitled) (Revista de Artes Marciales Asiáticas, 2021)
Traditional martial art is a pivotal part of Chinese folk culture. However, due to the impact of modern culture, the inheritance of various martial arts is threatened. Therefore, many efforts have been made by the Chinese government to protect this unique culture in the late 20th century. To provide practical indications for the safeguard of intangible cultural heritage, we conducted a literature review for the Chinese strategies concerning the safeguard of traditional martial arts (TMA) in the past 30 years, also tried to identify the advantages and shortcomings of current safeguard of TMA. Existing evidence indicates that the legislative safeguarding of Chinese TMA has gradually evolved into a system for preservation. Modern devices are important to maintain the current form of the intangible cultural heritage. Inviting inheritors of the TMA to teach relevant skills and knowledge in university campuses may play an important role in the dynamic safeguard of inheritance. On the other hand, shortcomings are also noticed. For instance, younger generations are not fully aware of the importance of TMA, thus specific education is needed. The means of transmission of TMA is still insufficient in the current information era.